A linguagem poética na tradução da Eneida de Carlos Alberto Nunes: um estudo na perspectiva da teoria tradutória de Haroldo de Campos - Colares, Francisca Tânia Almeida (2018)
Carlos Alberto Nunes (1897-1990) translated in 1981 the Aeneid of Virgil forging a hexametric verse that would correspond to the dactylic hexameter of Virgil. The hexameter of Nunes is predominantly dactylic, with sixteen poetic syllables and ictus falling at 1st, 4th, 7th, 10th, 13th and 16th, resulting in a tonic followed by two atonic, compounding the dactylic foot; the 16th syllable can be itself a foot or be accompanied by an atonic syllable, resulting in a trochee foot; to vary the rhythm of declamation, the hexameter of Nunes can present trihemimeral, penthemimeral and hephthemimeral caesuras. In the opinion of the critic Haroldo de Campos (1929 – 2003), Nunes’ labor is worthy consideration for his verses, otherwise, concerning language, it is not an undertakig aiming at new solutions. Haroldo de Campos believes that creative texts such as poetry or poetic prose, should be recreated, taking into consideration the phonic plan, the syntax, visual aspects, i.e., the dance of the words. In this process, the translator-recreator acts like the designer of the word. Considering Campos’ assertation, this work intends to analyze the translation process of Nunes, observing the expression form and content form, important aspects for a creative translation, in Campos’ opinion. The justification for this research lies in the fact that it approaches Nunes’ translation through the translating process. There are studies and papers about Nunes’ translations, but their aim is at the critic of the vernacular hexameter forged by Nunes. To analyze the translation process we observe the elocution in Virgil’s composition in the source text, in the excerpt Aen. 2.3-68 and Aen. 2.199-227 compared to the expression and the content forms in the target text. Our hypothesis is that the long verse dactilic hexameter of Nunes did not favor the recreation of language. The translator would always need to insert another word to complete the sixteenth poetic syllables and would not work on the poetry of the translation. With this research we expect to identify that Nunes worked on language in his translation, otherwise he did not translate the poem in a way that could be considered a recreation, i. e., he did not follow Campos’ theory.